Salvinialean megaspores in the Late Cretaceous of southern Patagonia, Argentina - Santamarina, Patricio Emmanuel (2018)
We report here two megaspores species related to the aquatic ferns of the Order Salviniales from the Late Cretaceous Mata Amarilla Formation (Austral Basin), southern Santa Cruz Province, Argentina. They were assigned to the species Arcellites disciformis and Balmeisporites cf. B. holodictyus. The presence of A. disciformis, in particular, is significant not only because it represents the first record for the Southern Hemisphere, indicating a bi-hemispheric distribution for the species, but it also increases the diversity of this genus in Patagonia. The new record enlarge the importance of water ferns in the Late Cretaceous landscapes of southern South America by adding the presence of a new species. The common occurrences of Arcellites and Balmeisporites, whether in shallow, fresh or brackish water facies, support a local aquatic paleoenvironment for the Mata Amarilla Formation, as was also suggested by the sedimentological evidence. They also allow referring the lower and middle levels of the Mata Amarilla Formation to the Chronostratigraphic Zone M3 (Albian-Cenomanian) defined for the cretaceous of Patagonia on the bases of its megaspore content.